The equivalent elastic parameters: A lozenge grid structure with negative Poisson's ratio. (September 2019) - Wang, S; Li, Z; Zhou, K F; Tan, Q W
Abstract: A new kind of chiral stent was designed by three-dimensional lozenge grid structure structure with four ligaments. Based on the conventional beam theory and energy conservation principle, in-plane Poisson's ratio and equivalent Young's modulus are derived, and finite element analysis was employed to validate the analytical estimates of the elastic module. Then the FEM models are used to investigate the elastic deformation behaviours of lozenge grid structure. The calculated results of equivalent elastic modulus based on beam theory are in consistent with those obtained by finite element method. The theoretical and numerical results show that lozenge grid structure stent proposed in this paper is negative Poisson's ratio material. The presented theory could be used in designing new hierarchical honeycomb structures for multifunctional applications.